HUBUNGAN LOBBY AMBASSADOR DAN KUALITAS PELAYANAN TAMU VIP DI DEPARTEMEN FRONT OFFICE PADA HOTEL GRAND HYATT JAKARTA - Azzahra Putri Larasati; Roy Daniel Samboh (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
This study aims to determine the relationship between the Ambassador Lobby and VIP guest service quality in the front office department at the Grand Hyatt Jakarta hotel in terms of the 5 dimensions of service quality, namely: tangibles, reliability, responsiveness, empathy. (emphaty), and assurance (assurance). This type of research is descriptive with the method of job analysis. For this job analysis method using a data collection process that analyzes a job or activity directly. This data collection technique is carried out by coming directly, and observing and analyzing it yourself. Based on the results of the research and discussion, it can be seen that the Ambassador Lobby is related to the quality of service for VIP guests at the Grand Hyatt Jakarta hotel. The author uses descriptive research methods and quantitative approaches and is processed using the Validity Test, Reliability Test, and Spearman's Rank Correlation Test, whereby using this research method it will be known that there is a significant relationship between variables (X) and variable (Y) to be studied so that it makes conclusions that will clarify the description of the object under study. The conclusion of this study is that the Ambassador Hotel Grand Hyatt Jakarta Lobby has many advantages, behind these advantages there are also disadvantages. However, these deficiencies can be minimized by improving services for VIP guests at the Grand Hyatt Jakarta hotel